ANALISIS PROSES BISNIS KENAIKAN PANGKAT PADA DINAS PERTANIAN, PERKEBUNAN DAN KETAHANAN PANGAN KABUPATEN BONE BOLANGO - Rizal Lamusu (Universitas Muhammadiyah Gorontalo, 2021)
In the process of filing the promotion of civil servants at the Office of Argriculture. Plantation and Food Security Bone Bolango regency experienced the problems because the data or file civil servants are not stored in the field officials in Agriculture, Plantation and Food Security, Bone Bolango regency and data collection on the promotion of civil servants still do manually or conventional so takes long time. This research aims to simplify and accelerate the process of conducted with using the Research and Development (R and D) as well as development of systems using Bussiness Process Model Natotation (BPMN). The result in this reserach showed gaps and opportunities for increase the business process in the Office of Agriculture, Plantation and Food Security in Bone Bolango regenvy that includes major activities and supporting activity. This research can be developed in the form of base web, mobile web, and security system.